Os conceitos fundamentais da crítica marxista do direito de Evgeni Pachukanis - Alvares de Farias, João Guilherme (Revista Direito e Práxis, 2022)
DOI: 10.1590/2179-8966/2021/57061 RESENHA Os conceitos fundamentais da crítica marxista do direito de Evgeni Pachukanis AKAMINE JR. et al. Léxico Pachukaniano. 1. ed. Marília-SP: Lutas Anticapital, 2020. 272 p. ISBN 978-65-86620-35-1. João Guilherme A. de Farias¹ ¹ Universidade Federal de São Paulo (EFLCH), Guarulhos, São Paulo, Brasil. E-mail: alvares.farias@unifesp.br. ORCID: https://orcid.org/0000-0001-7488-8370.